ANALISIS PENGARUH EKSPOR DAN UTANG LUAR NEGERI TERHADAP CADANGAN DEVISA DI INDONESIA PERIODE 2000-2021 - Putri Sari M J Silaban (Niagawan, 2022)
The purpose of this study is to analyze the effect of exports and international debt on Foreign Exchange Reserves in Indonesia in 2000-2021. The data used in this study is secondary data time series obtained from the Badan Pusat Statistik and Bank Indonesia. The data analysis used is the classical assumption test (normality test, multicollinearity test, heteroscedasticity test and autocorrelation test), multiple linear regression and statistical tests (test coefficient of determination (R²), t test and F test) using the E-Views 10 application as analysis tool. Our results obtained Exports and Foreign Debt By simultaneously affect the foreign exchange reserves in Indonesia with a significance level α = 5% probability of F statistics obtained value probability of F statistics obtained value <α (0.05) ie 0.000 <0.05. Partially Export positive and significant impact on foreign exchange reserves, and Foreign Debt positive and significant impact on foreign exchange reserves. Variations of factors that influence the foreign exchange reserves is explained by exports and the Foreign Debt jointly effect of 96%. This means that approximately 94% of foreign exchange reserves is explained by the variable Exports and Foreign Debt.